IMPLIKASI TAUHID TERHADAP TATANAN DALAM POLITIK PERSPEKTIF ISMAIL RAJI AL-FARUQI - Jupri Zadauta (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2018)
As for what is in this research is 1. How is the concept of monotheism in perspective Ismail Raji Al-Faruqi? 2. How are the implications of monotheism on the perspective of the political perspective Ismail Raji Al-Faruqi?. The results of research on the Tawhid Implications of the Perspective Political Order Ismail Raji Al-Faruqi. Stating 1) Tawheed according to Ismail Raji Al-Faruqi in a simple and traditional way, namely: Beliefs and testimonies that there is no God but Allah. The name of God is God and occupies a central position in every position, action and thought of every Muslim. Tawhid is also a general view of reality, the world, space and time, human history and destiny. 2) Monotheistic implications of the political order is to develop a system of government that can bring closer and fulfill the Divine will, namely a system based on the Qur’an and Sunnah. While the Caliphate was built based on the agreement of three dimensions, namely agreement of insight, agreement of will and agreement of action.